Antagonistic Activity of Lactic Acid Bacteria Against Pathogenic Vibrios and Their Potential Use as Probiotics in Shrimp (Penaeus vannamei) Culture - Thompson, John; Weaver, Mark A.; Lupatsch, Ingrid; Shields, Robin J.; Plummer, Sue; Coates, Christopher J.; Rowley, Andrew F. (Frontiers in Marine Science, 2022)
Probiotic use in aquaculture settings can be a tool for disease control and dietary supplementation. We assessed the antagonistic effect of culture supernatants of lactic acid bacteria on the growth of known shrimp pathogens, Vibrio (Listonella) anguillarum, Vibrio alginolyticus and V. harveyi, using a quantitative microplate bioassay. Supernatants from Lactobacillus curvatus subsp. curvatus, L. plantarum and Pediococcus acidolactici significantly inhibited the growth of these vibrios. The active component(s) were heat stable (>100 ºC) and resistant to freeze-thawing. Most of this inhibitory activity was brought about by the production of an acid pH, however, there was evidence for other factors playing a role. In the search for novel probiotic bacteria, an organism was isolated from the gastrointestinal tract of healthy whiteleg shrimp, Penaeus vannamei, that was identified tentatively as Carnobacterium maltaromaticum. This isolate, however, had less potent vibriocidal activity than the lactic acid bacteria and caused a reduction in survival when injected into shrimp at a dose of 1 x107 bacteria/shrimp. During a 28-day feeding trial, L. plantarum supplemented feed given to juvenile P. vannamei showed no gross changes in the growth parameters of these animals compared with the control group. We contend that lactic acid bacteria could be incorporated into biofloc formulations to purge the growth of pathogenic vibrios in pond settings, rather than being fed directly to shrimp.